2019
DOI: 10.1021/acs.chemrestox.9b00371
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect between Human Papillomavirus 18 and 4-(Methylnitrosamino)-1-(3-pyridyl)-1-butanone on Malignant Transformation of Immortalized SHEE Cells

Abstract: 4-(Methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) is an important tobacco-specific nitrosamine (TSNA) that induces malignant tumors in rodents. High-risk human papillomavirus (hr-HPV) infection is an important cause of several human cancers. Epidemiological evidence has shown that HPV cooperatively induces carcinogenesis with tobacco smoke. In the present study, the synergistic carcinogenesis of NNK and HPV18 was investigated. Immortalized human esophageal epithelial SHEE cells containing the HPV18 E6E7 gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…However, few evidences have been provided for the DNA alkylation by NNK in HPV-infected cells. In the present and our previous studies [21], we consistently observed that the level of total POB-DNA adducts in HPV-positive cells was significantly higher than that in HPV-negative cells, suggesting synergistic carcinogenesis of HPV and NNK. Moktar et al [45] reported that single-and double-strand DNA breaks induced by cigarette smoke condensate were dose-dependent and persistent in HPV-transformed human ectocervical cells, which gave support to our results.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…However, few evidences have been provided for the DNA alkylation by NNK in HPV-infected cells. In the present and our previous studies [21], we consistently observed that the level of total POB-DNA adducts in HPV-positive cells was significantly higher than that in HPV-negative cells, suggesting synergistic carcinogenesis of HPV and NNK. Moktar et al [45] reported that single-and double-strand DNA breaks induced by cigarette smoke condensate were dose-dependent and persistent in HPV-transformed human ectocervical cells, which gave support to our results.…”
Section: Discussionsupporting
confidence: 85%
“…Immortalized human esophageal epithelial cells (SHEE) were purchased from the BeNa Culture Collection (BNCC) Biotechnology Company (Beijing, China) and were transfected with the HPV-18 E6E7 gene (SHEE-E6E7) or with empty vector (SHEE-V) by lentiviral transfection described in our previous study [21]. Cells were cultured using Dulbecco's Modified Eagle Medium (DMEM, Hyclone, South Logan, UT, USA) supplemented with 10% fetal bovine serum (FBS, DAKEWE, Shenzhen, China) and 1% penicillin and streptomycin (Hyclone, South Logan, UT, USA).…”
Section: Cell Culturementioning
confidence: 99%
See 2 more Smart Citations
“…71 The latest findings indicated that NNK and HPV18 exhibit a synergistic effect on malignant transformation of esophageal epithelial cells. 72 This evidence suggested that HPV is not the independent risk factor of EC, combined with the fact of high nitrosamine exposure in Huai'an. 73 HPV18 infection Het-1A stable transfected cell model was established, and then Het-1A-HPV18 cells were exposed to MNNG in our study.…”
Section: Discussionmentioning
confidence: 97%